Collagen–nanofiber hydrogel composites promote contact guidance of human lymphatic microvascular endothelial cells and directed capillary tube formation 1. Issue 6 (30th November 2012) - Laco, Filip; Grant, M. Helen; Black, Richard A.
Abstract: Collagen and fibronectin matrices are known to stimulate migration of microvascular endothelial cells and the process of tubulogenesis, but the physical, chemical, and topographical cues for directed vessel formation have yet to be determined. In this study, growth, migration, elongation, and tube formation of human lymphatic microvascular endothelial cells (LECs) were investigated on electrospun poly(D, L ‐lactic‐ co ‐glycolic acid) (PLGA) and poly(L ‐lactic‐ co ‐D ‐lactic acid) (PLDL) nanofiber‐coated substrates, and correlated with fiber density and diameter. Directed migration of LECs was observed in the presence of aligned nanofibers, whereas random fiber alignment slowed down migration and growth of LECs. Cell guidance was significantly enhanced in the presence of more hydrophobic PLDL polymer nanofibers compared to PLGA (10:90). Subsequent experiments with tube‐forming assays reveal the ability of resorbable hydrophobic nanofibers >300 nm in diameter to promote cell guidance in collagen gels without direct cell–fiber contact, in contrast to the previously reported contact‐guidance phenomena. Our results show that endothelial cell guidance is possible within nanofiber/collagen–gel constructs that mimic the native extracellular matrix in terms of size and orientation of fibrillar components. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.